2017
DOI: 10.15560/13.2.2101
|View full text |Cite
|
Sign up to set email alerts
|

Range extension of Lundomys molitor (Winge, 1887) (Mammalia: Rodentia: Cricetidae) to eastern Rio Grande do Sul state, Brazil

Abstract: Abstract:The distribution range of Lundomys molitor, a cricetid rodent species known from only six localities, herein is extended about 295 km with the inclusion of a record from Rio Grande do Sul state. The new locality represents the easternmost limit of the distribution of this poorly studied species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…In addition, differences in molar morphology have been highlighted between the Lagoa Santa material and living samples (Pardiñas & Teta, 2011). More important to the focus of the present study, Brandão & Fegies (2017) reported subtle differential traits between individuals from SLS and Uruguay. In this context, the nominal form Holochilus magnus, erected by Hershkovitz (1955) with a type locality in eastern Uruguay, deserves attention for its potential value in a much needed revision of Lundomys.…”
Section: Semi-deciduous Seasonal Forests In the Brazilian Pampa: Smalmentioning
confidence: 68%
See 1 more Smart Citation
“…In addition, differences in molar morphology have been highlighted between the Lagoa Santa material and living samples (Pardiñas & Teta, 2011). More important to the focus of the present study, Brandão & Fegies (2017) reported subtle differential traits between individuals from SLS and Uruguay. In this context, the nominal form Holochilus magnus, erected by Hershkovitz (1955) with a type locality in eastern Uruguay, deserves attention for its potential value in a much needed revision of Lundomys.…”
Section: Semi-deciduous Seasonal Forests In the Brazilian Pampa: Smalmentioning
confidence: 68%
“…Although we uncritically referred the studied Lundomys material to the single species today recognized for the genus, L. molitor (Winge, 1887), it is important to note that the species has its type locality in Lagoa Santa, Minas Gerais, about 1,500 km northeast of SLS, where it became extinct (Voss & Carleton, 1993;. Today, L. molitor is mostly known from populations in the Uruguayan territory and three adjacent Brazilian localities (Silveira et al, 2011;Voss, 2015;Brandão & Fegies, 2017). In addition, differences in molar morphology have been highlighted between the Lagoa Santa material and living samples (Pardiñas & Teta, 2011).…”
Section: Semi-deciduous Seasonal Forests In the Brazilian Pampa: Smalmentioning
confidence: 99%
“…Selected noticeable examples are the Quaternary occurrence of Lundomysregistered from Minas Gerais in Brazil (Voss and Carleton 1993) to southern Buenos Aires Province in Argentina (Pardinas and Teta 2011). Its widespread past range (covering more than 15 degrees of latitude) contrast with its current geographic distribution restricted to less than 10 recording localities in Uruguay and southernmost Brazil (Voss 2015b, Brandao andFegies 2017). Large populations belonging toHolochilus have been recorded in Holocene deposits (Nuapua locality) of southern Bolivian Chaco (Pardinas and Galliari 1998) where today is neither Holochilus nor permanent water (Coltorti et al 2012).…”
mentioning
confidence: 99%